CNN Indonesia's Framing Strategy in Influencing Public Opinion - Juidah, Imas; Pratiwi, Veronika Unun (UIR Press, 2025)
This study analyzes media framing in political reporting by CNN Indonesia from January to July 2024, focusing on how the media frames political events related to the government's position. Media framing plays a role in shaping public opinion, but studies on framing patterns in Indonesia's mainstream media are still limited. This study aims to identify CNN Indonesia's framing patterns on political issues and how the media builds narratives that strengthen or challenge the government's legitimacy. Using Entman's (1993) and Pan & Kosicki's (1993) framing analysis with a qualitative approach, this study found that CNN Indonesia tends to support the government on issues of democratic stability, while on controversial issues such as the change in the age limit for regional head candidates, the framing emphasizes public reaction and policy criticism. The conclusion of this study shows that media framing influences public opinion, both in strengthening the government's position and highlighting dissatisfaction with controversial policies, making it important to critically analyze political media coverage in Indonesia.